Tummy time without the tears: The impact of parent positioning and play. Issue 4 (20th May 2020) - Mendres‐Smith, Amber E.; Borrero, John C.; Castillo, Mariana I.; Davis, Barbara J.; Becraft, Jessica L.; Hussey‐Gardner, Brenda
Abstract : The American Academy of Pediatrics (AAP) recommends that infants spend supervised time in the prone (tummy) position to foster motor development and prevent cranial deformities. However, infants may not tolerate the position, and consequently, caregivers may avoid placing their infants in the prone position. The AAP recommends that caregivers provide toys or interaction during tummy time. We evaluated the individual and combined effects of a play mat and experimenter interaction on negative vocalizations and head elevation during tummy time—positive effects were limited. Next, we evaluated a parent‐led intervention wherein mothers interacted with their infants, using a toy, while lying chest‐to‐chest. This intervention was associated with a reduction in negative vocalizations and an increase in head elevation for the majority of infants. Additionally, mothers rated the effectiveness of the parent‐led intervention more favorably than the experimenter‐led intervention, suggesting the effects of the parent‐led intervention were also socially valid.